The Content of Forming Speaking Competencies of Primary Class Students on The Base of Innovative Technologies (Journal of Pedagogical Inventions and Practices, 2023)
In primary classes, especially in the 1st grade students, it is desirable to systematically carry out the formation of speech competences with various methods and tools. It is an important task to make every student a literate, fluent speaker and free thinker It takes a lot of work and time. Innovative technologies, traditional and non-traditional educational methods, educational tools, ICT tools help us in this